Methods used in mobile applications for the diagnosis of hearing loss: A systematic mapping study - Vizcaíno Hebert Leonidas, Atencio; Perdomo Verónica Paulina, Tintín; Caizabuano José Rubén, Caiza; Altamirano Fernando Sebastián , Caicedo (KnE Engineering, 2020)
Hearing loss is one of the most common health problems today, it can appear at any age and the causes are varied, in order to prevent it or adapt to the changes brought about by the hearing impairment, it is necessary to diagnose it in time. The technology in terms of applications for health care smartphones has constantly evolved, so that today play an important role and are among the most downloaded from application stores, several of these applications are the diagnosis of hearing loss and use the method of pure tones. In this study a Systematic Mapping of Literature SMS (Systematic Mapping Study) is made to look for mobile applications that use other diagnostic methods that offer similar or better results, of the 13 applications found, 11 used the method of pure tones and in only 2 of them was implemented the speech audiometry (word recognition), concludes that diagnostic hearing loss tests based on mobile applications are reliable alternatives to conventional audiometric systems, and that pure tone thresholds alone are an incomplete assessment of hearing, and there is a need to develop new hearing measurement methods and combine them with other methods to complement the diagnosis. Resumen: La pérdida de la audición es uno de los problemas de salud más comunes en la actualidad, puede aparecer a cualquier edad y las causas son variadas, para poder prevenirla o adaptarse a los cambios que conlleva la deficiencia auditiva, es necesario diagnosticarla a tiempo. La tecnología en cuanto a aplicaciones para smartphones de asistencia de salud ha evolucionado constantemente, tal es así que hoy en día juegan un papel importante y son de las más descargadas de las tiendas de aplicaciones, varias de esas aplicaciones son las de diagnóstico de pérdida auditiva y utilizan el método de los tonos puros. En este estudio se hace un Mapeo Sistemático de Literatura SMS (Systematic Mapping Study) para buscar aplicaciones móviles que utilicen otros métodos de diagnóstico que ofrezcan similares o mejores resultados, de las 13 aplicaciones encontradas, 11 utilizaron el método de los tonos puros y en solo 2 de ellas se implementó la logoaudiometria (reconocimiento de palabras), por lo que se concluye que las pruebas de diagnóstico de pérdida auditiva basadas en aplicaciones móviles, son alternativas confiables a los sistemas de audiometría convencionales, y que los umbrales de tonos puros por sí solos son una evaluación incompleta de la audición, y existe la necesidad de desarrollar nuevos métodos de medición de audición y combinarlos con otros métodos para complementar el diagnóstico.